THE IMPACT OF MOBILE MONEY ON ECONOMIC GROWTH IN UGANDA - MUKYALA TRINY ASHLEY C (My University, 2024)
This dissertation looks at how the introduction of mobile money in Uganda has economically impacted the country by focusing mainly on how it has contributed to financial inclusion, poverty reduction and its role in agriculture development. It has caused a great change in Uganda’s financial sector since it has enabled people living in areas that have limited access to the usual banking services to efficiently carry out their financial transactions because mobile money is easily accessible and safe. Therefore, there has been an increase in financial transactions in the country, including transactions of people residing in rural areas. This study analyzes the relationship between mobile money use and economic growth in Uganda with descriptive statistics, correlation analysis and regression analysis using secondary data from sources such as the Bank of Uganda and the World Bank. The research explores how the number and value of mobile money transactions affect financial inclusion and poverty reduction. It also shows that mobile money plays a key role in increasing financial inclusion by supporting savings, providing access to credit and facilitating financial transactions. There are also some challenges faced with the use of mobile money which are addressed with recommendations made to policy-makers in order to try and solve them. Nonetheless, mobile money should be maximized in order for the country to reap its full benefits.